Effects of exercise on angiogenesis biomarkers in cancer patients: a systematic review and meta-analysis - Wang, Jingyu; He, Yuxuan; Wang, Ziqian; Wang, Zhouluo; Sun, Yu; Lee, Kyung-Hee; Choi, Jae-Young (Frontiers in Immunology, 2026)
ObjectiveAngiogenesis plays a central role in tumor growth, progression, and treatment response. The primary aim of this systematic review and meta-analysis was to determine the effects of regular exercise on angiogenesis biomarkers in patients with cancer.MethodsRandomized controlled trials (RCTs) were searched across five databases up to July 2025. Eligible studies included adults with cancer (≥18 years), exercise interventions lasting more than four weeks, and at least one reported angiogenesis biomarker. The Cochrane risk of bias tool was used to assess RCT quality, and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach was applied to evaluate evidence certainty. Meta-analysis and meta-regression were performed using robust variance estimation.ResultsThirteen RCTs were included. Pooled estimates suggested a small, nonsignificant difference in circulating VEGF favoring exercise (d = −0.14, p = 0.36). Similarly small, nonsignificant differences were observed for VCAM-1 (d = 0.24, p = 0.15) and MCP-1 (d = −0.20, p = 0.36).ConclusionRegular exercise was associated with only small and nonsignificant changes in angiogenesis biomarkers in patients with cancer. Although these preliminary patterns suggest potential interactions with angiogenic and immune pathways, the low certainty of evidence limits firm conclusions. Future randomized controlled trials are needed to confirm these effects and clarify how exercise prescriptions at different treatment stages influence angiogenesis. Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251088092.